Corrections to Phytotaxa 230: New species and new combinations in Micromeria (Lamiaceae) from the Canary Islands and Madeira - Puppo, Pamela; Meimberg, Harald (Phytotaxa, 2015)
Following the publication of New species and new combinations in Micromeria (Lamiaceae) from the Canary Islands and Madeira (Puppo & Meimberg 2015), two necessary corrections were brought to our attention.